Surrealism in Latin America : Vivísimo Muerto - Ades, Dawn; Eder, Rita; Speranza, Graciela (LA; Getty Research Institute, 2012)
This collection of essays the first major account of surrealism in Latin America that covers both literary and visual production explores the role the movement played in the construction and recuperation of cultural identities and the ways artists and writers contested, embraced, and adapted surrealist ideas and practices.
English
Keywords: N5300-7418 Visual Arts- History